2021
DOI: 10.1007/s13311-021-01082-x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Gene and Small Molecule Therapies for the Neurodevelopmental Disorder Angelman Syndrome

Abstract: Angelman syndrome (AS) is a rare (~1:15,000) neurodevelopmental disorder characterized by severe developmental delay and intellectual disability, impaired communication skills, and a high prevalence of seizures, sleep disturbances, ataxia, motor deficits, and microcephaly. AS is caused by loss-of-function of the maternally inherited UBE3A gene. UBE3A is located on chromosome 15q11–13 and is biallelically expressed throughout the body but only maternally expressed in the brain due to an RNA antisense transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 156 publications
(184 reference statements)
0
14
0
Order By: Relevance
“…Two categories of therapeutic strategies are being actively pursued for Angelman syndrome. One is to target the downstream substrates of UBE3A protein, and the other is to restore UBE3A gene expression ( Margolis et al, 2015 ; Yang, 2020 ; Copping et al, 2021 ; Elgersma and Sonzogni, 2021 ; Markati et al, 2021 ). Since the paternal UBE3A allele is intact in Angelman syndrome, an attractive approach is to reactivate the silenced paternal UBE3A by suppressing UBE3A-ATS expression ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Two categories of therapeutic strategies are being actively pursued for Angelman syndrome. One is to target the downstream substrates of UBE3A protein, and the other is to restore UBE3A gene expression ( Margolis et al, 2015 ; Yang, 2020 ; Copping et al, 2021 ; Elgersma and Sonzogni, 2021 ; Markati et al, 2021 ). Since the paternal UBE3A allele is intact in Angelman syndrome, an attractive approach is to reactivate the silenced paternal UBE3A by suppressing UBE3A-ATS expression ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…For imprinting disorders, the discovery that topoisomerase inhibitors can reactivate the abnormally silenced allele in an Angelman syndrome mouse model (Huang et al 2011 ) led to the realization that targeting an antisense transcript would be a viable therapeutic strategy in Angelman syndrome. Multiple strategies are underway to capitalize on this, including actively recruiting multi-center trials (Copping et al 2021 ). For MDEMs, two independent publications showed that the memory defect identified in a mouse model of Rubinstein-Taybi syndrome (caused by haploinsufficiency of a writer of histone acetylation) could be improved with postnatal histone deacetylase (HDAC) inhibition, helping break the dogma that intellectual disability cannot be treated in postnatal life (Alarcon et al 2004 ; Bourtchouladze et al 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical ramifications include etiologically specific neurodevelopmental trajectories with opportunities for targeted early intervention and, potentially, the development of genetically guided pharmacological interventions [ 29 , 162 ]. For example, Angelman syndrome is a rare neurodevelopmental disorder involving severe developmental delay, intellectual disability and seizures, resulting from loss of function of the maternally inherited UBE3A gene on chromosome 15q11–13 [ 163 ]. Emerging small molecule drug and gene therapies involve restoration of UBE3A function [ 164 ].…”
Section: Discussionmentioning
confidence: 99%